(untitled) (Docentes 2.0 Journal, 2021)
To advocate for a culture of peace in a country and a region historically marked by violence is a challenge that must initiate from the schools; these circumstances raise the need to include the La Paz chair in the academic curriculum and face this perspective. The objective of this research focused on analyzing the incidence of the conflict resolution theory of Johan Galtung, which enunciates the concepts of conflict and peace and refers to concrete actions to reduce or eradicate conflicts and favor environments of healthy coexistence the recovery of a culture of peace. Various pedagogical and didactic strategies mediated the application of this theory: Fanzineros for la Paz web page, MY DIARY booklet, diagnostic and exit forms, and tests. The methodology used was qualitative, being the most accurate to investigate social phenomena in which specific objectives are pursued to respond to problems. The population with whom developed the research was between 13 and 14 years of age; it is a group of 34 students. As a result, it was possible to show a decrease in the rates of school violence and, therefore, an improvement in school coexistence and human relations. The main conclusion indicates the re-establishment of a culture of peace, understood as the appropriation of knowledge and citizen skills to construct a healthy coexistence.